Digital Teaching in Photonics – new possibilities for Labwork Training Programs - Kaiser, Thomas; Lin, Tzu Huan; Kretzschmar, Johannes; Soika, Falko; Michel, Joerg; Helgert, Christian; Geiss, Reinhard; Pertsch, Thomas; Tünnermann, Andreas (Optics InfoBase Conference Papers, 2021)
New technologies rapidly lead to many new possibilities for digital teaching concepts of labwork training programs, which might be on-site or remotely. Mixed Reality is a promising candidate to meet the learning goals.
CRIS-Team Scopus Importer:2023-04-20